ENHANCING FOR VOCABULARY MASTERY THROUGH MNEMONICS KEYWORD METHOD TO THE UNIVERSITY STUDENTS - Susana, Intan (Universitas Nusantara PGRI Kediri, 2017)
This research is focused on mnemonic keyword method to enhance vocabulary mastery to the university students. Mnemonic refers to instructional or learning strategies designed specifically to enhance memory. One of the most powerful mnemonic strategies is the key word method. The keyword method is a useful mnemonic aid which can help broaden students’ vocabulary by means of speech and ultimately with reading and writing. Then keyword method effective way to provide a meaningful visual image upon which to base memory for a new word's meaning. This research involves twenty students at the first grade. The research instruments of this study are consisted of tests, observation checklist, and a questionnaire. This study was class action research. From the cycle 1 reflection result, some procedures and activities were revised. Different from the cycle 2, the researcher used mnemonic keyword method and there is no reflection. The enhancement of students’ vocabulary mastery shows with individual test and got mean score 67.75 in the cycle 1 and 79.75 in the cycle 2.In addition the enhancement of students’ vocabulary mastery in group test and got mean score 72.00 in the cycle 1 and increased to be 81.00 in the cycle 2. In this result, it shows there enhancement for vocabulary mastery through mnemonic keyword method in the first grade students at STKIP PGRI Blitar.